Preparation method of degradable environment-friendly ceramic tile

Through the intermittent wet ball milling and water-based casting forming process, the raw material ratio and ball milling parameters are adjusted to prepare ceramic tiles that can be degraded under wet conditions, solving the problem that ceramic tiles are not easy to degrade in humid environments and achieving efficient degradation and wear resistance, meeting environmental protection and personalized needs.

CN119161168AInactive Publication Date: 2024-12-20ZIBO GOLD LION KING TECH CERAMICS CO LTD

Patent Information

Application Number
CN202411357607.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing ceramic tiles are not easy to degrade under wet conditions, resulting in high environmental pollution and industrial costs, and the traditional preparation process is inefficient, making it difficult to meet environmental protection and personalized needs.

Method used

The batch wet ball mill and water-based casting molding process are used to adjust the raw material ratio and ball mill parameters, and ceramic tiles are prepared through high-temperature kiln segment calcination. Polyvinyl alcohol and glycerol are used as binders and plasticizers to improve the degradation of ceramic tiles. and wear resistance.

Benefits of technology

Ceramic tiles can achieve a degradation rate of 95% under natural conditions, and while ensuring wear resistance, it reduces processing power consumption, achieving the goal of environmental protection and energy saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064072470000061
    Figure BDA0005064072470000061
Patent Text Reader

Abstract

The invention discloses a preparation method of a degradable environment-friendly ceramic tile, and belongs to the technical field of ceramic tile preparation. The preparation method comprises the following steps: sequentially adding the raw materials in parts by weight into a ball mill, carrying out intermittent wet ball milling for 4-5 hours, sieving to obtain slurry, and preparing a blank by utilizing a water-based tape casting method; and finally, firing the blank in a high-temperature kiln to cure the blank into the ceramic tile. The method is simple in process, power consumption during processing is reduced, the purposes of energy conservation and emission reduction are achieved, and the method can be used for large-scale industrial production. After the ceramic tile prepared by the method is crushed and naturally placed for one year under natural conditions, the degradation rate can reach 95%, the wear resistance of the ceramic tile is not obviously reduced on the premise of ensuring environmental protection and degradability, and the basic wear resistance requirement in the use process can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tile preparation, and in particular relates to a method for preparing degradable and environmentally friendly ceramic tiles. Background Art

[0002] Ceramics is a material with a long history and wide application, which is composed of clay and other inorganic non-metallic raw materials. Its unique properties and various preparation methods make it an ideal choice in many fields, especially in the architectural ceramics industry. Ceramic products such as ceramic tiles (floor tiles, exterior wall tiles, etc.), ceramic panels and sculptures are widely used in indoor and outdoor decoration as well as walls and floors of buildings. They are not only beautiful and durable, but also have good thermal insulation and sound insulation properties, and are an important part of modern architecture. Ceramic tiles are easy to construct, easy to maintain, wear-resistant and non-slip, and have unique physical properties and decorative effects. They are widely used in various types of buildings, but they are also inevitably accompanied by large amounts of waste and waste. The chemical properties of ceramic tiles are stable and not easy to degrade, which poses a severe challenge to the natural environment.

[0003] With the increasing demand for people's quality of life, increasingly fierce market competition and increasingly stringent environmental protection policies, new requirements have been put forward for the environmental protection and personalization of ceramic tiles. Patent CN108863324 A discloses a preparation scheme for a degradable low-temperature co-fired ceramic, which uses SiO2, SiO2·nH2O, H3BO3, B2O3, NaOH, KOH, Ba(OH)2·8H2O, Al(OH)3, MgO, CaO, SrO, ZnO and rare earth oxides as raw materials, and obtains the product through ball milling, drying, grinding, calcining, granulation, molding and sintering process steps. The invention uses water as the trigger phase for ceramic degradation, and the ceramics obtained by this method are not suitable for application in southern my country and under humid conditions. Therefore, in order to reduce environmental pollution and save industrial costs, it is necessary to explore a new method for preparing degradable and environmentally friendly ceramic tiles. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing a degradable and environmentally friendly ceramic tile.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] Step 1: Add the raw materials in portions into a ball mill for intermittent wet ball milling. After 4-5 hours of ball milling, sieve to obtain slurry.

[0007] Step 2: The slurry in step 1 is made into a rough blank by water-based tape casting method.

[0008] Step 3: Firing the roughcast in a high-temperature kiln to solidify it into a ceramic tile

[0009] Preferably, the raw materials in step 1 are calculated by weight: 30-36 parts of kaolin, 20-25 parts of quartz sand, 10-15 parts of clay, 10-15 parts of silicon dioxide, 5-10 parts of borax, 1-2 parts of barium oxide, 3-5 parts of light calcium carbonate, 4-8 parts of magnesium oxide, 1-2 parts of boron trioxide, 1-2 parts of silicon carbonate, 1-3 parts of strontium carbonate, 1-2 parts of zirconium oxide, and 2-3 parts of rich borax.

[0010] Preferably, the intermittent ball milling method in step 1 is specifically as follows: feeding materials in proportion into a ball mill, and setting the ball milling in four stages: the speed of the first stage is set to 480 rpm for grinding for 0.5 hour; the speed of the second stage is set to 650 rpm for grinding for 2 hours; the speed of the third stage is set to 480 rpm for grinding for 1.5-2 hours.

[0011] Preferably, the feeding ratio in the ball mill is balls: material: water = 30:46:24.

[0012] Preferably, polyvinyl alcohol is added as a binder and glycerol is added as a plasticizer during the ball milling process.

[0013] Preferably, the sieving is 200 mesh.

[0014] Preferably, the water-based tape casting method in step 2 is specifically to use a scraper to scrape and apply the slurry obtained in step 1 to a certain thickness on the base tape, peel off the film of the green tape from it after drying and curing, and then punch and laminate the green tape to make a finished blank to be sintered.

[0015] Preferably, in step 3, the high temperature kiln is calcined in stages

[0016] In the first stage, the high temperature kiln is heated from room temperature to 300-360°C at a rate of 10-15°C / min and calcined in nitrogen for 2-3.5 hours.

[0017] In the second stage, the high temperature kiln is heated from 300-360°C to 700-800°C at a rate of 15-25°C / min and calcined in nitrogen for 6-7 hours.

[0018] In the third stage, the high temperature kiln is heated from 700-800°C to 1150-1250°C at a rate of 10-15°C / min and calcined in nitrogen for 2-3.5 hours.

[0019] The beneficial effects of the present invention include the following aspects:

[0020] (1) The present invention adjusts the ratio of each raw material to adjust the degradation triggering condition of the ceramic tile to degradation after crushing under air humidity, thereby increasing the application range of the ceramic tile.

[0021] (2) The degradation rate of the ceramic bricks made by this method can reach 35-45% in the second half of the year under natural conditions after being crushed, and the degradation rate can reach 95% after being placed naturally for one year.

[0022] (3) This method uses intermittent wet ball milling to reasonably control the time and rotation speed of different stages in the ball milling, which significantly improves the ball milling efficiency, reduces the power consumption during processing, and achieves the purpose of energy saving and emission reduction.

[0023] (4) The traditional film compression molding process has poor uniformity and low efficiency. The application of the tape casting process has realized the continuity and automation of production and improved the quality of ceramic tiles. DETAILED DESCRIPTION

[0024] Example 1

[0025] According to the weight components, 30 parts of kaolin, 20 parts of quartz sand, 15 parts of clay, 10 parts of silicon dioxide, 7 parts of borax, 2 parts of barium oxide, 5 parts of light calcium carbonate, 5 parts of magnesium oxide, 1 part of boron trioxide, 1 part of silicon carbonate, 1 part of strontium carbonate, 1 part of zirconium oxide, and 1 part of rich borax were weighed as raw materials, and the feeding ratio was aluminum ball: material: water = 30:46:24, and then polyvinyl alcohol was added as a binder and glycerol as a plasticizer. First, the speed was set to 480 rpm and ground for 0.5 hours; then the speed was set to 650 rpm and ground for 2 hours; finally, the speed was set to 480 rpm, and after grinding for 2 hours, the slurry was obtained by passing through a 200-mesh sieve.

[0026] The slurry obtained in step one is applied to the base tape with a scraper in a certain thickness. After drying at 110° C. for 10 hours, the film of the green tape is peeled off from the base tape. The green tape is then punched and laminated to form a finished blank to be sintered.

[0027] The rough blank is first placed in a high-temperature kiln and the temperature is raised from room temperature to 300-360°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours; secondly, the temperature is raised from room temperature to 700-800°C at a rate of 15-25°C / min, and calcined in nitrogen for 6 hours; finally, the temperature is raised from room temperature to 1150-1250°C at a rate of 10-15°C / min, and calcined in nitrogen for 3.5 hours to solidify into ceramic tiles.

[0028] Example 2

[0029] According to the weight components, 33 parts of kaolin, 22 parts of quartz sand, 10 parts of clay, 10 parts of silicon dioxide, 10 parts of borax, 2 parts of barium oxide, 3 parts of light calcium carbonate, 5 parts of magnesium oxide, 1 part of boron trioxide, 1 part of silicon carbonate, 1 part of strontium carbonate, 1 part of zirconium oxide, and 1 part of rich borax were weighed as raw materials, and the feeding ratio was aluminum ball: material: water = 30:46:24, and then polyvinyl alcohol was added as a binder and glycerol as a plasticizer. First, the speed was set to 480 rpm and ground for 0.5 hours; then the speed was set to 650 rpm and ground for 2 hours; finally, the speed was set to 480 rpm, and after grinding for 1.8 hours, the mud was passed through a 200-mesh sieve to obtain mud.

[0030] The slurry obtained in step one is applied to the base tape with a scraper in a certain thickness. After drying at 110° C. for 10 hours, the film of the green tape is peeled off from the base tape. The green tape is then punched and laminated to form a finished blank to be sintered.

[0031] The rough blank is first placed in a high-temperature kiln and the temperature is raised from room temperature to 300-360°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours; secondly, the temperature is raised from room temperature to 700-800°C at a rate of 15-25°C / min, and calcined in nitrogen for 6 hours; finally, the temperature is raised from room temperature to 1150-1250°C at a rate of 10-15°C / min, and calcined in nitrogen for 3.5 hours to solidify into ceramic tiles.

[0032] Example 3

[0033] According to the weight components, 34 parts of kaolin, 22 parts of quartz sand, 10 parts of clay, 10 parts of silicon dioxide, 7 parts of borax, 2 parts of barium oxide, 3.5 parts of light calcium carbonate, 5 parts of magnesium oxide, 1.5 parts of boron trioxide, 1.5 parts of silicon carbonate, 1.5 parts of strontium carbonate, 1 part of zirconium oxide, and 1 part of rich borax were weighed as raw materials, and the feeding ratio was aluminum ball: material: water = 30:46:24, and then polyvinyl alcohol was added as a binder and glycerol as a plasticizer. First, the speed was set to 480 rpm and ground for 0.5 hours; then the speed was set to 650 rpm and ground for 2 hours; finally, the speed was set to 480 rpm, and after grinding for 1.5 hours, the mud was passed through a 200-mesh sieve to obtain mud.

[0034] The slurry obtained in step one is applied to the base tape with a scraper in a certain thickness. After drying at 110° C. for 10 hours, the film of the green tape is peeled off from the base tape. The green tape is then punched and laminated to form a finished blank to be sintered.

[0035] The rough blank is first placed in a high-temperature kiln and the temperature is raised from room temperature to 300-360°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours; secondly, the temperature is raised from room temperature to 700-800°C at a rate of 15-25°C / min, and calcined in nitrogen for 6 hours; finally, the temperature is raised from room temperature to 1150-1250°C at a rate of 10-15°C / min, and calcined in nitrogen for 3.5 hours to solidify into ceramic tiles.

[0036] Example 4

[0037] According to the weight components, 28 parts of kaolin, 21 parts of quartz sand, 15 parts of clay, 10 parts of silicon dioxide, 8 parts of borax, 2 parts of barium oxide, 5 parts of light calcium carbonate, 5 parts of magnesium oxide, 1 part of diboron trioxide, 1 part of silicon carbonate, 1 part of strontium carbonate, 1 part of zirconium oxide, and 1 part of rich borax were weighed as raw materials, and the feeding ratio was aluminum ball: material: water = 30:46:24, and then polyvinyl alcohol was added as a binder and glycerol as a plasticizer. First, the speed was set to 480 rpm and ground for 0.5 hours; then the speed was set to 650 rpm and ground for 2 hours; finally, the speed was set to 480 rpm, and after grinding for 2 hours, the mud was passed through a 200-mesh sieve to obtain mud.

[0038] The slurry obtained in step one is applied to the base tape with a scraper in a certain thickness. After drying at 110° C. for 10 hours, the film of the green tape is peeled off from the base tape. The green tape is then punched and laminated to form a finished blank to be sintered.

[0039] The rough blank is first placed in a high-temperature kiln and the temperature is raised from room temperature to 300-360°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours; secondly, the temperature is raised from room temperature to 700-800°C at a rate of 15-25°C / min, and calcined in nitrogen for 6 hours; finally, the temperature is raised from room temperature to 1150-1250°C at a rate of 10-15°C / min, and calcined in nitrogen for 2 hours to solidify into ceramic tiles.

[0040] Example 5

[0041] According to the weight components, 30 parts of kaolin, 20 parts of quartz sand, 15 parts of clay, 10 parts of silicon dioxide, 7 parts of borax, 2 parts of barium oxide, 5 parts of light calcium carbonate, 5 parts of magnesium oxide, 1 part of boron trioxide, 1 part of silicon carbonate, 1 part of strontium carbonate, 1 part of zirconium oxide, and 1 part of rich borax were weighed as raw materials, and the feeding ratio was aluminum ball: material: water = 30:46:24, and then polyvinyl alcohol was added as a binder and glycerol as a plasticizer. First, the speed was set to 480 rpm and ground for 0.5 hours; then the speed was set to 650 rpm and ground for 2 hours; finally, the speed was set to 480 rpm, and after grinding for 1.5 hours, the slurry was obtained by passing through a 200-mesh sieve.

[0042] The slurry obtained in step one is applied to the base tape with a scraper in a certain thickness. After drying at 110° C. for 10 hours, the film of the green tape is peeled off from the base tape. The green tape is then punched and laminated to form a finished blank to be sintered.

[0043] The rough blank is first placed in a high-temperature kiln, and the temperature is raised from room temperature to 300-360°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours; secondly, the temperature is raised from room temperature to 700-800°C at a rate of 15-25°C / min, and calcined in nitrogen for 6 hours; finally, the temperature is raised from room temperature to 1150-1250°C at a rate of 10-15°C / min, and calcined in nitrogen for 3 hours to solidify into ceramic tiles.

[0044] The ceramic tiles prepared in the above examples were subjected to performance tests.

[0045] Degradation rate

[0046] The ceramic bricks fired in Examples 1-5 were broken into blocks, and the existing common ceramic bricks were used as a comparative example, and placed in a natural environment for one year. The weight before and after the placement was weighed every 60 days to calculate the weight loss rate. The test results are shown in Table 1.

[0047] Table 1

[0048]

[0049] Wear resistance

[0050] Taking the existing common ceramic bricks as comparative examples, the ceramic bricks prepared in the above Examples 1 to 5 were subjected to wear resistance tests. The test results are shown in Table 2.

[0051] Table 2

[0052] Group Wear-resistant revolutions Example 1 15350 Example 2 14258 Example 3 15012 Example 4 14015 Example 5 14925 Comparative Example 14623

[0053] It can be seen from the above table that the ceramic tiles obtained by the embodiments described in the present invention not only have a good degradation rate, but also have no significant reduction in wear resistance while ensuring environmental protection and degradability, and can meet the basic wear resistance requirements during use.

[0054] The above description is made in conjunction with the embodiments of the present invention, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many changes without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a degradable and environmentally friendly ceramic tile, characterized in that: include Step 1: Add the raw materials in portions into a ball mill for intermittent wet ball milling. After 4-5 hours of ball milling, sieve to obtain slurry. Step 2: The slurry in step 1 is water-based tape-cast to form a rough blank. Step 3: Fire the rough blank in a high-temperature kiln to solidify it into a ceramic tile.

2. The method for preparing the degradable and environmentally friendly ceramic tile according to claim 1, characterized in that: The raw materials in step 1 are calculated by weight: 28-35 parts of kaolin; 20-25 parts of quartz sand; 10-15 parts of clay; 10-15 parts of silicon dioxide; 5-10 parts of borax; 1-2 parts of barium oxide; 3-5 parts of light calcium carbonate; 4-8 parts of magnesium oxide; Boron trioxide 1-2 parts; 1-2 parts of silicon carbonate; 1-3 parts of strontium carbonate; 1-2 parts of zirconium oxide; 2-3 parts of rich borax.

3. The preparation method according to claim 1, characterized in that: The intermittent ball milling method in step 1 is specifically as follows: the materials are added in proportion in the ball mill, and the ball milling is set to four stages: the speed of the first stage is set to 480 rpm, and the grinding is performed for 0.5 hours; the speed of the second stage is set to 650 rpm, and the grinding is performed for 2 hours; the speed of the third stage is set to 480 rpm, and the grinding is performed for 1.5-2 hours.

4. The ball milling method according to claim 3, characterized in that: The feed ratio in the ball mill is ball: material: water = 30:46:

24.

5. The ball milling method according to claim 3, characterized in that: Polyvinyl alcohol was added as a binder and glycerol as a plasticizer during the ball milling process.

6. The preparation method according to claim 1, characterized in that: The sieving is 200 meshes.

7. The preparation method according to claim 1, characterized in that: The water-based tape casting method in step 2 is specifically to use a scraper to apply the slurry obtained in step 1 to a certain thickness on the base tape, and after drying and curing, peel off the film of the green tape from the top, and then punch and laminate the green tape to make a finished blank to be sintered.

8. The preparation method according to claim 1, characterized in that: In step 3, the high temperature kiln is calcined in stages In the first stage, the high temperature kiln is heated from room temperature to 300-360°C at a rate of 10-15°C / min and calcined in nitrogen for 2-3.5 hours. In the second stage, the high temperature kiln is heated from 300-360°C to 700-800°C at a rate of 15-25°C / min and calcined in nitrogen for 6-7 hours. In the third stage, the high temperature kiln is heated from 700-800°C to 1150-1250°C at a rate of 10-15°C / min and calcined in nitrogen for 2-3.5 hours.

9. The preparation method according to any one of claims 1 to 8 can produce degradable and environmentally friendly ceramic tiles.

Citation Information

Patent Citations

  • Method for preparing magnetizable ceramic

    CN102153333A

  • Formula of environmental protection brick and production method thereof

    CN103641392A

  • Pug for low temperature firing environmental-friendly degradable ceramic, low temperature firing environmental-friendly degradable ceramic and manufacturing method of low temperature firing environmental-friendly degradable ceramic

    CN105693203A

  • Vitrified tile produced by using waste fiber glass filaments and production method of vitrified tile

    CN106810208A

  • Natural degradable ceramic material and preparation method thereof

    CN115286362A

Cited By

  • High-hardness synthetic fossil porcelain for daily use and production process thereof

    CN119349982A